Bestandserfassung und -überwachung des atlanto-skandischen Herings. EU-Studie "Hydroacoustic Surveys of Atlanto-Scandian Herring in the Norwegian Sea, 1998-2000 (ASH-II)" - Hammer, Cornelius (1998)
The atlanto-scandian herring consists of two major stocks, i.e. the Icelandic summer spawner and the Norwegian spring spawner. Both stocks have recovered well after complete collapse in the seventies and allow for a controlled fishery. The total allowable catch of the Norwegian spring spawner is currently 1.3 mill. t. The resumption of the fishery is accompanied by an annual and multi-national survey with Norwegian, Faeroe Islands, Icelandic and Russian contribution. In 1998 the EU will contribute to the survey with the Swedish vessel ”Argos” and in 1999 with the ”Walther Herwig III” under Dutch, Swedish and German participation. About half of the survey costs are covered by the EU by means of a funded study, the other half is contributed by the participating nations.